ANGKA KEJADIAN OBESITAS SENTRAL PADA WANITA DI DESA TUMALUNTUNG - Ticoalu, Maria A. Ch.; Wongkar, Djon; Pasiak, Taufiq F. (Universitas Sam Ratulangi, 2015)
Abstract: Central obesity is a condition of excess abdominal fat (central fat) caused by direct factors that causes central obesity such as lack of physical activity, therefore, more fat accumulation occurs in the abdomen. Central obesity also increases the risks of degenerative diseases. This was a descriptive study. Data were obtained by measuring weight and height, calculating the body mass index (BMI), and measuring waist circumference (â‰¥80 cm) of 180 females aged 30-50 years in the Tumaluntung village. The data were counted manually. The results showed that of the population there were 0.6 % underweight, 19.4 % normal body weight, 12.2 % pre - obese, 42.8 % Obese I, 24.4 % Obese II, and 0.6 % Obese III. Based on BMI, 80% of the subjects were overweight meanwhile based on waist circumference there were 66.7 % of females with central obesity.Keywords: central obesity, BMI, waist circumferenceAbstrak: Obesitas sentral adalah kondisi kelebihan lemak perut (lemak pusat) yang terjadi akibat kurangnya aktifitas fisik sehingga akumulasi lemak lebih banyak terjadi di bagian perut. Obesitas sentral juga meningkatkan resiko terjadinya penyakit degeneratif. Penelitian ini bersifat deskriptif. Data diperoleh dari pengukuran berat badan dan tinggi badan, penghitungan indeks massa tubuh (IMT) serta lingkar pinggang (â‰¥80 cm) pada 180 populasi wanita berusia 30-50 tahun di Desa Tumaluntung. Data yang diperoleh dihitung secara manual. Hasil yang diperoleh dari 180 subyek penelitian menunjukkan 0,6% underweight, 19,4% normal, 12,2% pre-obese, 42,8% Obese I, 24,4% Obese II, dan 0,6% Obese III. Berdasarkan perhitungan IMT terdapat 80% subyek penelitian mengalami kelebihan berat badan. Melalui pengukuran lingkar pinggang terdapat 66,7% wanita dengan obesitas sentral.Kata kunci: obesitas sentral, IMT, lingkar pinggang